2009
DOI: 10.1889/jsid17.8.665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient illuminance on users' visual performance using various electronic displays

Abstract: Abstract— This study investigated the effect of ambient illuminance (50, 500, 1500, 3000, 6000, and 9000 lx) on participants' visual performance using four electronic displays (conventional LCD under transmissive mode, conventional LCD under reflective mode, Ch‐LC display, and E‐ink display). Analysis results indicate that participants' visual performance shows significant difference under various ambient illuminance and electronic displays. The interaction between ambient illuminance and electronic display al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…The VDTs with backlit or some form of integrated light unit were more readable at lower levels of illuminance compared with reflective displays. As expected, the evaluations for the LCD (iPad) were higher at lower levels of illuminance but dropped above the 500 lx level, while the reverse was true for the reflective device (Kindle DX) . As with other studies, the evaluations of the reading of conventional paper increased until the 2000 lx level .…”
Section: Discussionsupporting
confidence: 77%
“…The VDTs with backlit or some form of integrated light unit were more readable at lower levels of illuminance compared with reflective displays. As expected, the evaluations for the LCD (iPad) were higher at lower levels of illuminance but dropped above the 500 lx level, while the reverse was true for the reflective device (Kindle DX) . As with other studies, the evaluations of the reading of conventional paper increased until the 2000 lx level .…”
Section: Discussionsupporting
confidence: 77%
“…For an LCD, linear polarizers form an integral component of the system and, as light valves, the pixel drive states can change reflected light properties. In our emulations, we did not attempt to reproduce the differences in reflected light that can occur with different pixel architectures and contrast enhancement films …”
Section: Discussionmentioning
confidence: 99%
“…The procedure of this study was similar to that of our previous studies. 15,[10][11][12] In each trial, participants were asked to distinguish the direction of the Landolt-C gap on the display to evaluate their visual acuity. The size of the Landolt-C was designed to evaluate the visual acuity of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…They 10 also indicated that an ambient illuminance higher than 700 lx up to 1500 lx when using the e-paper display will enhance performance. Wang et al 11 also posited that higher ambient illuminance (500 lx) for the e-ink display may result in superior visual performance, whereas substantially higher ambient illuminance (1500 lx) for the Ch-LC display may achieve better visual performance. Wang et al 12 found that participants exhibited the best preference under high ambi-ent illuminance (500 lx).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation